How Do Legal Experts Cope With Medical Reports and Forensic Evidence? The Experiences, Perceptions, and Narratives of Swiss Judges and Other Legal Experts - Canela, Carlos; Buadze, Anna; Dube, Anish; Jackowski, Christian; Pude, Ingo; Nellen, Romilda; Signorini, Paola; Liebrenz, Michael (Frontiers in Psychiatry, 2019)
Expert scientific knowledge, including medical knowledge, is relevant for the legal profession and can strongly influence rulings and sentencing in criminal law, civil law and insurance law. The way in which this medical evidence is understood and evaluated thus has an impact both on individuals and on society as a whole. It enters legal procedures in various forms, for example, as expert witness statements and/or as a legal expert’s own acquired medical knowledge. On the other hand, a legal expert may be confronted with medical opinions that differ in quality or content and thus have to decide which ones to follow. The aim of this qualitative study was to investigate legal experts’ perceptions, experiences, and narratives regarding medical knowledge, particularly the skills and general knowledge used in their branch of the legal profession. A total of 51 semi-structured interviews with judges and prosecutors from different courts of law and from the public prosecutor's office in six different cantons of Switzerland were conducted, coded, and analyzed using Nvivo. We used a comparison thematic approach identifying common and new themes related to the research aims. Our findings suggest that judges and prosecutors believe that possessing and developing the skills and terminology required for processing medical information is important but complex, and time-consuming for their work. Additionally, several legal experts reported that their understanding of medical evidence was limited or even non-existent. Moreover, the acquisition of skills related to the assessment of medical reports and forensic evidence appeared to be unstructured. Participants reported having no formal instruction in how to evaluate or deal with medical knowledge. The sources they used to answer questions arising appeared to be in part problematic and non-standardized. Medical literature from peer-reviewed journals was used only rarely. The findings from this study suggest that law departments might wish to evaluate whether their graduates are sufficiently equipped with scientific literacy skills and appropriate skills to evaluate medical information for their later careers. At the same time, medical knowledge pertinent to forensics published in local legal journals may be more effective in reaching the legal expert audience than in medical journals.